Evaluation of 14 Accessions of Amaranthus cruentus for Production of Early Vegetative Yield - oyekale, kehinde oluwaseun (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The present study was conducted to identify cultivar(s) of Amaranthus cruentus with the ability for production of vegetative yield within a short period of growth. A total of fourteen accessions of Amaranthus Cruentus were evaluated at 4weeks, 6weeks, 8weeks and 10weeks after planting (WAP) for plant height, leaf number, fresh and dry weights of leaves, stem and branches to measure the relative performance of the accessions. The experiment was planted, using a randomized complete block design (RCBD), with the Amaranthus cruentus as the treatment. The result showed significant differences in all the traits evaluated at each harvest period. The result also indicates significant variation in the ability of the accessions for early and rapid production of early vegetative yield. Three potentially suitable accessions BAM18, BAM 13, and BAM 22 were identified based on their outstanding performances at 4WAP and 6WAP harvest. Further field trial is required before they can be recommended for commercial production by farmers. Keywords: Vegetative Yield, Accessions, Cultivars, Traits.